Preadmission Statin Therapy and Clinical Outcome in Hospitalized Patients With COVID-19: An Italian Multicenter Observational Study. Issue 1 (July 2021) - Russo, Vincenzo; Silverio, Angelo; Scudiero, Fernando; Attena, Emilio; D'Andrea, Antonello; Nunziata, Luigi; Parodi, Guido; Celentani, Dario; Varbella, Ferdinando; Albani, Stefano; Musumeci, Giuseppe; Di Micco, Pierpaolo; et al.
Abstract : Abstract: Statin therapy has been recently suggested as possible adjuvant treatment to improve the clinical outcome in patients with coronavirus disease 2019 (COVID-19). The aim of this study was to describe the prevalence of preadmission statin therapy in hospitalized patients with COVID-19 and to investigate its potential association with acute distress respiratory syndrome (ARDS) at admission and in-hospital mortality. We retrospectively recruited 467 patients with laboratory-confirmed COVID-19 admitted to the emergency department of 10 Italian hospitals. The study population was divided in 2 groups according to the ARDS diagnosis at admission and in-hospital mortality. A multivariable regression analysis was performed to assess the risk of ARDS at admission and death during hospitalization among patients with COVID-19. A competing risk analysis in patients taking or not statins before admission was also performed. ARDS at admission was reported in 122 cases (26.1%). There was no statistically significant difference for clinical characteristics between patients presenting with and without ARDS. One hundred seven patients (18.5%) died during the hospitalization; they showed increased age (69.6 ± 13.1 vs. 66.1 ± 14.9; P = 0.001), coronary artery disease (23.4% vs. 12.8%; P = 0.012), and chronic kidney disease (20.6% vs. 11.1%; P = 0.018) prevalence; moreover, they presented more frequently ARDS at admission (48.6% vs. 19.4%; P < 0.001). At multivariable regression model, statin therapy was not associated neither with ARDS at admission nor with in-hospital mortality. Preadmission statin therapy does not seem to show a protective effect in severe forms of COVID-19 complicated by ARDS at presentation and rapidly evolving toward death.